1991
DOI: 10.1111/j.1365-2958.1991.tb00828.x
|View full text |Cite
|
Sign up to set email alerts
|

Repression and induction of the nag regulon of Escherichia coll K‐12: the roles of nagC and nagA in maintenance of the uninduced state

Abstract: The nag regulon located at 15.5 min on the Escherichia coli chromosome consists of two divergent operons, nagE and nagBACD, encoding genes involved in the uptake and metabolism of N-acetylglucosamine. Null mutations have been created in each of the genes by insertion of antibiotic resistance cartridges. The phenotypes of the strains carrying the insertions in nagE, B and A were consistent with the previous identification of gene products: nagE, EII(Nag), the N-acetylglucosamine specific transporter of the phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
160
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(170 citation statements)
references
References 42 publications
9
160
0
1
Order By: Relevance
“…By analogous procedures, the non-polar cat (Cm r ) cassette (cf. Plumbridge, 1991) from pCM7 was inserted into the same HindIII of kpsF as that used for mutagenesis with the Km r cassette to yield pSX390, followed by construction of the suicide vector pSX405 and allelic exchange with the wild-type copy in EV36 to generate strain EV508. Southern hybridization analysis of ScaI-digested DNA isolated from EV36, EV500 and EV508 confirmed that the mutants contained the expected kpsF disruptions (results not shown).…”
Section: Insertion Mutagenesis Of Kpsfmentioning
confidence: 99%
“…By analogous procedures, the non-polar cat (Cm r ) cassette (cf. Plumbridge, 1991) from pCM7 was inserted into the same HindIII of kpsF as that used for mutagenesis with the Km r cassette to yield pSX390, followed by construction of the suicide vector pSX405 and allelic exchange with the wild-type copy in EV36 to generate strain EV508. Southern hybridization analysis of ScaI-digested DNA isolated from EV36, EV500 and EV508 confirmed that the mutants contained the expected kpsF disruptions (results not shown).…”
Section: Insertion Mutagenesis Of Kpsfmentioning
confidence: 99%
“…Strain NM522 was used for cloning experiments. Other E. coli strains used are 11814 (MG1655 ⌬lac) (A. Vianney), IBPC536 (thrA1 leuB6 hisG4 argE3 ⌬(gpt-lac)62 thi-1 galK2 ara-14 xyl-5 mtl-1 tsx-33 kdgK51 rpsL31 supE44 recB21 recC22 sbcB15 sbcC201 nagC::tc) (19), TK821 (MC4100 ompR::Tn10) (8), MV679 (MG1655 ⌬lacZYA ⌬nanR) (I. Blomfield), PHL1242 (MG1655 ⌬cpxR) (G. Jubelin), pop4129 (zhd::Tn10 ⌬crp18) (J.-C. Lazzaroni), and IBPC1016 (JM101 mlc::tc nanR6) (20).…”
Section: Methodsmentioning
confidence: 99%
“…However, the molecular details of curli gene repression by GlcNAc-6P remain unknown. NagC is thought to be a functional regulator only in the absence of GlcNAc since NagC-GlcNAc-6P binds DNA poorly (40). In the absence of nagA, GlcNAc-6P accumulates in the cell (55) and binds to NagC, preventing NagC-mediated repression at the nag promoters (40).…”
Section: Vol 188 2006mentioning
confidence: 99%
“…NagC acts as a transcriptional repressor of the nag genes when GlcNAc is not available (36,38,40). A role for NagD in GlcNAc metabolism and transport has not been identified.…”
mentioning
confidence: 99%